2020
DOI: 10.1158/0008-5472.can-20-1072
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Vaccine Encoding Shared Cancer Neoantigens to Treat Tumors with Microsatellite Instability

Abstract: Tumors with microsatellite instability (MSI) are caused by a defective DNA mismatch repair system that leads to the accumulation of mutations within microsatellite regions. Indels in microsatellites of coding genes can result in the synthesis of frameshift peptides (FSP). FSPs are tumor-specific neoantigens shared across patients with MSI. In this study, we developed a neoantigen-based vaccine for the treatment of MSI tumors. Genetic sequences from 320 MSI tumor biopsies and matched healthy tissues in The Canc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 51 publications
4
57
0
Order By: Relevance
“…Recently, we and others showed the induction of neoepitope-directed immune responses after vaccination with shared, in silico-predicted neoepitopes in mice (Leoni et al, 2020) and a clinical trial with mismatch repair-deficient patients (Kloor et al, 2020). Moreover, it was shown that T cells, re-activated by immune checkpoint inhibition, target tumor-specific neoepitopes thus further emphasizing the crucial role of HLA class I-presented neoepitopes in immunotherapeutic strategies (Gubin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we and others showed the induction of neoepitope-directed immune responses after vaccination with shared, in silico-predicted neoepitopes in mice (Leoni et al, 2020) and a clinical trial with mismatch repair-deficient patients (Kloor et al, 2020). Moreover, it was shown that T cells, re-activated by immune checkpoint inhibition, target tumor-specific neoepitopes thus further emphasizing the crucial role of HLA class I-presented neoepitopes in immunotherapeutic strategies (Gubin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, InDel neoepitopes have been suggested to possess higher immunogenicity caused by their fundamental difference to endogenous self-antigens originating from wild-type (WT) proteins (Turajlic et al, 2017). Several studies support the presence of InDel neoepitope-specific cytotoxic T cells in both healthy individuals and patients with MSI CRC (Leoni et al, 2020;Roudko et al, 2020;Schwitalle et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These findings demonstrated that indels generate a higher number of neoantigens than SNVs, thereby increasing the odds of neoantigen-associated immune activation and surveillance of tumor cells. Since every patient can have a peculiar mutational landscape, Leoni and collaborators analyzed 320 MSI tumor biopsies from TGCA, observing that 209 frameshift peptides were shared between patients [ 101 ]. In addition, considering an additional 20 MSI tumor patients, they identified 31 peptides in common with the initial cohort.…”
Section: Introductionmentioning
confidence: 99%
“…One heavily pretreated patient with bulky metastases showed stable disease over 7 months. A phase I trial with a vaccine encoding various frameshift peptides shared among MSI tumors is ongoing (NCT04041310) [ 111 ]. Vaccines could be combined with ICI such as proposed in phase I KEYNOTE-603 (NCT03313778) testing mRNA-4157 with Pembrolizumab with an acceptable tolerance and 8 out 20 patients experienced disease control.…”
Section: Overcoming Resistance To Immunotherapymentioning
confidence: 99%